2019
DOI: 10.1104/pp.19.00730
|View full text |Cite
|
Sign up to set email alerts
|

A Rice Transcription Factor Controls Grain Length through Cell Number

Abstract: Yield-related QTLs and their applications in rice genetic improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Another important yield component in rice is the 1,000-grain weight. However, it is more specific to the genotype than a response to fertilization (Cox & Smith, 2019). As demonstrated in Table 2, this study also found that the applied Si on 1,000-grain weight was nonsignificant over the control.…”
Section: Effect Of Silicon On Yield Attributes Of Ricesupporting
confidence: 54%
“…Another important yield component in rice is the 1,000-grain weight. However, it is more specific to the genotype than a response to fertilization (Cox & Smith, 2019). As demonstrated in Table 2, this study also found that the applied Si on 1,000-grain weight was nonsignificant over the control.…”
Section: Effect Of Silicon On Yield Attributes Of Ricesupporting
confidence: 54%
“…The increase of panicle length affected the yield. This condition, due to each panicle, affected the branches of grain stalk that produced more grain [20]. The length of a panicle of rice in SRI method was longer than the conventional method [8].…”
Section: A Length Of Paniclementioning
confidence: 95%
“…The grain counts per panicle at the mature stage are critical data for rice breeding research and yield assessment [ 1 , 2 ]. Additionally, it is viewed as one of the key traits for genetic improvement of rice yield [ 3 , 4 , 5 ]. Therefore, detection of the number of grains per panicle of rice is of great importance.…”
Section: Introductionmentioning
confidence: 99%